Information-seeking on the internet during the transition to motherhood: descriptive survey, Cyprus - Middleton, Nicos; Koliandri, I.; Kolokotroni, Ourania; Hadjigeorgiou, Eleni; Christodoulides, Veronica; Nicolaou, Christiana; Kouta, Christiana; Karanikola, Maria; Middleton, Nicos (My University, 2022)
Internet use in pregnancy is very prevalent. However, there are issues with information quality as well as acceptance by healthcare providers which can add to the frustration.
Keywords: pregnancy; healthcare provider